Peran Politis Gereja Masehi Injili di Halmahera (GMIH) pada Pemilu 2024 - Puasa, Anselmus; Noya, Meidy A.R.; Nanuru, Ricardo Freedom (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study aims to map the political role of the Gereja Masehi Injili di Halmahera (GMIH) in the 2024 Election and examine how the interaction between religion and politics affects the political preferences and participation of church members. This study employed a qualitative approach. Data were collected through open-ended surveys and in-depth interviews to gain a deeper understanding of the perspectives and experiences of church members. The findings reveal that members’ political preferences are strongly influenced by church leaders, the church actively mobilizes participation through value-based education, and maintains symbolic ties with certain candidates. GMIH contributes to strengthening local democracy but may risk polarization if neutrality is not maintained. Conclusion: GMIH plays a significant role in shaping political awareness and participation among members, with the potential to enhance local democracy if its influence is wisely managed.